Relationship between three methods for the evaluation of skeletal maturation with sexual maturation - Zapata, Óscar; Barbosa, Diana; Giraldo, Mónica; Gómez, Julia Andrea (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The objective of this study was to determine which of the methods used to establish the skeletal maturation is better related with the maturity of the patient, and for that reason is more practical and applicable to the clinical practice. The relationship between three different methods for evaluating the skeletal maturation through the hand-wrist film (Taranger and Hägg, Greulich and Pyle, and Fishman) and the sexual maturity (Tanner and Prader) was searched. A total of 33 patients were studied: 18 male and 15 female, between 8 and 13 years. Healthy children in Tanner I sexual maturity stage was the research criterion for inclusion. The 100% of both samples (masculine and feminine) were located in the F stage of skeletal development. Data were taken every six months during the course of three years (2000- 2002). In the male population there were no associations between the skeletal maturation evaluated according to Greulich and Pyle´s method, and Fishman´s method with the sexual maturity. On the other hand, an association was found between Taranger and Hägg´s method and the sexual maturity (sesamoid-general Tanner during the fourth sample and the middle phalanx of the third finger- right testicular volume during the same sample, as happened with the middle phalanx with both testicular volumes during de fifth sample). In the female population there were statistically significant associations between Fishman´s method and the sexual maturity during the second and sixth samples; also between Greulich and Pyle´s evaluation and the sexual maturity during the sixth sample. There was also an association between Taranger and Hägg´s method in the second, third and sixth samples (sesamoid-Tanner, middle phalanx-Tanner and sesamoid-Tanner respectively).